Location-Based Approach for Route Maintenance in Dynamic Source Routing Protocol - Sjaugi, Muhammad Farhan (2008)
Earlier, the idea of mobile computers and ad hoc networks was not on the mind of anyone. All speci¯cations and implementations for the computer networks during that time were designed for wired systems. This is a big challenge for computer engineer since these two systems have di®erent characteristics. Wireless network means dynamic topology, dynamic structure and no infrastructure, while wired network is the opposites. Basically mobile wireless network has the same stan- dard layers of structure, with modi¯cations and functionality that di®er from the earlier networks because of the absence of infrastructure. To facilitate communication within the network, a routing protocol is used to dis- cover routes between nodes. Building a MANET routing protocol is not an easy job, since e±ciency and correctness become the main concern. Some approach had been proposed to make routing protocol becomes e±cient and correct. Dynamic Source Routing (DSR) protocol is known to be a simple routing protocol in MANET. DSR is based on the concept of source routing. For this protocol, mobile nodes are required to maintain route caches that contain the source routes of which the mobile is aware. Entries in the route cache are continually updated as new routes are learned. There are two major phases of the protocol - route discovery and route maintenance Route discovery uses route request and route reply packets. Route maintenance uses route error packets and acknowledgments. Although DSR can respond a route quickly, it yields a long delay when a route is rebuilt. This is because when source node receives RERR packet, it will try to ¯nd alternative routes from route cache. If alternative routes are not available, source node, then, will enter route discovery phase to ¯nd new routes. Finding a route in wireless network require considerable resources, such as time, bandwidth, and power because it relies on broadcasting. In some case any packets may still reach its destination, but with some delay. This delay is very expensive and leads to undesired e®ect, especially in real time networks and the networks with QoS, where the packet delay and packet delivery is the main concern. The objectives of this research are to propose new algorithm to detect route failure as early warning message to the protocol to take further action, and to propose new algorithm for DSR route maintenance to response the early warning message from route failure detection algorithm. The proposed algorithms based on node location information that may be collected through Global Positioning System (GPS). This thesis introduces two new route maintenance strategies by utilizing node location information. These new route maintenance strategies are called as DIS- TANCE (DIstance baSed rouTe maintenANCE) and ADISTANCE (Adaptive DISTANCE). The algorithms work by adding another node (called bridge node) into the source list to prevent the link from failure. From the simulation result, both algoritmns improves the performance of DSR in terms of packet sending ratio, delay and routing overhead.This thesis introduces two new route maintenance strategies by utilizing node location information. These new route maintenance strategies are called as DIS- TANCE (DIstance baSed rouTe maintenANCE) and ADISTANCE (Adaptive DISTANCE). The algorithms work by adding another node (called bridge node) into the source list to prevent the link from failure. From the simulation result, both algoritmns improves the performance of DSR in terms of packet sending ratio, delay and routing overhead.